Redescription of Austinixa leptodactyla (Coelho, 1997) (Decapoda: Brachyura: Pinnotheridae) and synonymy of A. roblesi Palacios Theil & Felder, 2020, with an updated identification key to the genus - Oliveira, Amaury; Souza, Paulo Ricardo C.m. De; Souza-Filho, Jesser F.; Santana, William; Hernáez, Patricio (Zootaxa, 2026)
A comprehensive redescription of the pinnotherid crab, Austinixa leptodactyla (Coelho, 1997), is presented. The original description of this species is brief and supported by low-resolution illustrations, limiting its diagnostic utility. Here, we provide an updated and detailed redescription based on the holotype and additional material from Alagoas, Brazil. All diagnostic structures are fully illustrated. Examination of the holotype and paratypes of A. roblesi Palacios Theil & Felder, 2020, shows that these specimens agree with the holotype of A. leptodactyla in all key morphological traits. No consistent or diagnostic characters were detected that would support their separation as distinct taxa. Based on the currently available evidence, A. roblesi is here regarded as a junior synonym of A. leptodactyla. An updated identification key to the species of Austinixa is also provided.